Perfil da fluência de indivíduos com taquifemia - Oliveira, Cristiane Moço Canhetti de [UNESP]; Bernardes, Ana Paula Lazarin; Broglio, Gabriela Aparecida Fabbri [UNESP]; Capellini, Simone Aparecida [UNESP] (Pró-Fono Produtos Especializados para Fonoaudiologia Ltda., 2010)
TEMA: fluência na taquifemia. OBJETIVO: caracterizar e comparar a fluência de indivíduos com taquifemia com indivíduos fluentes. MÉTODOS: participaram dessa investigação 14 indivíduos na faixa etária de 8.0 a 40.11 anos de idade, de ambos os gêneros divididos em dois grupos, pareados por idade e gênero. GI foi composto por 7 indivíduos com taquifemia e GII por 7 indivíduos controles. Um protocolo de avaliação da fluência da fala foi utilizado para obter e analisar a amostra de fala, que considera a tipologia, a freqüência das disfluências e a velocidade de fala. RESULTADOS: os dados indicaram que os grupos se diferenciaram em relação às disfluências comuns e gagas, número de sílabas e de palavras por minuto. CONCLUSÃO: o perfil da fluência de indivíduos com taquifemia é muito distinto do perfil de falantes fluentes.

BACKGROUND: speech fluency in cluttering. AIM: to characterize and to compare the speech fluency in cluttering and fluent individuals. METHOD: participants of this investigation were 14 individuals with ages between 8.0 and 40.11 years, of both genders, divided into two groups, paired by age and gender. GI was composed by 7 cluttering individuals and GII by 7 fluent individuals. The Speech Fluency Assessment Protocol was used to gather and to analyze the speech samples, taking into consideration the typology and frequency of speech disruption (SLD and OD) and speech rate, in words and syllables per minute. RESULTS: data showed that the groups differed regarding the occurrence of the stuttering-like disfluencies and other disfluencies, number of words and syllables per minute. CONCLUSION: cluttering individuals present a different fluency profile when compared to their fluent pairs.
Speech fluency profile in cluttering individuals
Keywords: Fonoaudiologia; Fala; Diagnóstico; Speech; Language and Hearing Sciences; Speech; Diagnosis